2021
DOI: 10.3390/ijerph18020735
|View full text |Cite
|
Sign up to set email alerts
|

Methodological Approach of the Iron and Muscular Damage: Female Metabolism and Menstrual Cycle during Exercise Project (IronFEMME Study)

Abstract: Background: The increase in exercise levels in the last few years among professional and recreational female athletes has led to an increased scientific interest about sports health and performance in the female athlete population. The purpose of the IronFEMME Study described in this protocol article is to determine the influence of different hormonal profiles on iron metabolism in response to endurance exercise, and the main markers of muscle damage in response to resistance exercise; both in eumenorrheic, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 95 publications
0
38
0
Order By: Relevance
“…Based on the current considerations for research in sport and exercise science with women as participants [26], the first day of the menstrual cycle started with the onset of menstrual bleeding. Furthermore, eumenorrheic participants performed a urinary ovulation test (Ellatest, Alicante, Spain) to detect the luteinizing hormone surge occurring 24-36 h before ovulation from 3 days before the predicted ovulation day by the calendar-based counting method until a positive test was recorded, as previously indicated [26,27]. In accordance with this, participants with eumenorrheic cycles were evaluated during the mid-follicular phase (day 6 to 10 of the cycle) or during the mid-luteal phase (+5 to +9 days after confirmed ovulation).…”
Section: Menstrual Cycle Controlmentioning
confidence: 99%
“…Based on the current considerations for research in sport and exercise science with women as participants [26], the first day of the menstrual cycle started with the onset of menstrual bleeding. Furthermore, eumenorrheic participants performed a urinary ovulation test (Ellatest, Alicante, Spain) to detect the luteinizing hormone surge occurring 24-36 h before ovulation from 3 days before the predicted ovulation day by the calendar-based counting method until a positive test was recorded, as previously indicated [26,27]. In accordance with this, participants with eumenorrheic cycles were evaluated during the mid-follicular phase (day 6 to 10 of the cycle) or during the mid-luteal phase (+5 to +9 days after confirmed ovulation).…”
Section: Menstrual Cycle Controlmentioning
confidence: 99%
“…Consequently, it may affect the second question of MIS and deviate the score to be either zero or one in our ESRD subjects (normal or slightly less quantity of food intake). Iron deficiency presented in this study might also be affected by menstruation (Peinado et al, 2021 ). As a result, we suggested that our results should be interpreted with these considerations.…”
Section: Discussionmentioning
confidence: 57%
“…Participants possessed 7.4 ± 5.3 years of endurance training experience, with a training volume of 296 ± 184 min per week during the 6 months prior to recruitment. The calculation of the sample size suggested 21 participants to produce a statistical power of 0.80 with an effect size of 0.75 at a significance level of p < 0.05 (see calculation details here (Peinado et al 2021)). To be included in the study, participants were required to meet the following criteria: (i) healthy adult females between 18 and 40 years of age; (ii) naturally menstruating for the 6 months prior to the study, and during the study, to present with eumenorrheic cycles confirmed by peak luteinizing hormone (LH) and sex hormone concentrations; (iii) no consumption of medication that alters vascular function (e.g., tricyclic antidepressants, α-blockers, β-blockers, etc.)…”
Section: Participantsmentioning
confidence: 99%